ANALYSIS OF FOOD SAFETY ASSESSMENT INDICATORS (American Journal of Business Management, Economics and Banking, 2025)
In this scientific work, the state of food security in Uzbekistan was analyzed using statistical and econometric methods. In the study, the relationship between the production volumes of agricultural products, agriculture and livestock, food imports and levels of environmental pollution was studied using linear regression models. The results of the study show that while food imports have a positive impact on all production sectors, harmful substances emitted into the atmosphere have a negative impact. Based on the analysis, practical and theoretical proposals have been developed for the rational use of imported resources and the reduction of environmental pollution in ensuring food security.